Surface modification of kapton polyimide using a DC-powered ion shower system - Flores, Jose Cornelio M. (2011.)
Polyimide is one of the widely used materials for semiconductor and electronics application because of its excellent properties. However, there is a need for this material to be surface treated because it has poor adhesion during processing. Plasma surface modification treatment is one of the cleanest and most promising technologies available. This study aims to determine the contributions of the identified factors such as accelerating voltage, type of gas, exposure time , and gas filling pressure to the surface property changes induced by a DC-powered ion shower system using a 1/2 of 2⁴ fractional factorial design of experiment with replications. Kapton polyimide films with 0.05 mm thickness were plasma treated and response parameters for the treatment were measured such as contact angle for hydrophilic property or wettability, surface roughness by AFM, plasma stage current and Fourier Trasform Infrared Spectroscopy-Attenuated Total Reflectance (FTIR-ATR) spectra. The plasma stage current was used to compute an energy/pressure parameter from the product of the accelerating voltage, plasma stage current and exposure time divided by the gas filling pressure. results of the experiment showed that the significant main effects for contact angle response were exposure time and gas filling pressure. There were also two significant aliased 2-factor interaction effects. For surface roughness, all main effects were identified to be significant with three significant aliased 2-factor interaction effects. The plasma stage current response resulted to three significant main effects, namely, accelerating voltage, exposure time, and gas filling pressure. A single aliased 2-factor interaction effect was also noted. All the treatment combination decreased contact angle from an initial value of 60̊ with an average based on FTIR-ATR analysis. Surface roughness generally increased with an average of 45% and was within a few nanometers range using an Atomic Force Microscope. This makes the system very suitable for nanoprocessing of polyimide. The plot of contact angle versus the energy/pressure parameter point to an optimum level where contact angle becomes a minimum. This is at vicinity of 25 to 75 J/mTorr, a range defined by the actual optimum level from experimental data and the mimimum in the fitted trend curve. The plot of surface roughness versus energy parameter shows, however, a maximum roughness at around 50J/mTorr. From all the data gathered from this study, it was clearly shown that the DC-powere ion shower system is effective in surface modification of Kapton polyimide.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman
Keywords: Polyimides; Kapton (Trademark); Semiconductors; Ion implantation